Intramedullary craniovertebral junction tuberculoma: An uncommon location of a common disease - Rajendra S. Jain; Rahul Handa; Trilochan Srivastava; Swayam Prakash; Kadam Nagpal; Indu Bhana; Pankaj K. Gupta (Elsevier, 2014)
Summary: Central nervous system involvement is observed in no more than 10% of patients with systemic tuberculosis. Although CNS tuberculosis is not rare in endemic countries, such as India, intramedullary tuberculosis is not commonly reported. In this study, we report a case of a 40-year-old female who presented with a six-year history of insidious onset, gradually progressive, asymmetric quadriparesis. She was diagnosed with intramedullary tuberculoma at the craniovertebral junction and showed significant clinico-radiological improvement with medical management alone. To the best of our knowledge, this report describes the first case of intramedullary tuberculoma at the craniovertebral junction to be reported. With the increased availability of MRI in developing countries, it is now possible for clinicians to diagnose this condition without performing a biopsy. It is important for the clinicians in developed countries to be highly suspicious of intramedullary tuberculoma, as there has been a resurgence of CNS tuberculosis due to the emergence of the HIV pandemic. Keywords: Intramedullary, Tuberculoma, Craniovertebral junction